ANALISIS PENGARUH KEMISKINAN DAN PENGANGGURAN TERHADAP TINGKAT INDEKS PEMBANGUNAN MANUSIA DI PROVINSI NUSA TENGGARA BARAT TAHUN 2011-2020 - Muhammad Masruron (Al-Qardhu, 2022)
This study aims to determine the effect of poverty and unemployment on the level of the human development index in West Nusa Tenggara Province in 2011-2020. The method used in this research is descriptive quantitative with multiple regression analysis with the help of SPSS Ver. 20. Multiple regression can be seen from the partial, simultaneous and determination tests. The results of this study indicate that the poverty variable has a negative and significant effect on the level of the human development index in the Province of NTB in 2011-2020, while the unemployment variable has a negative and significant effect on the level of the human development index in the Province of NTB in 2011-2020. The results of the F test prove that all independent variables (poverty and unemployment) have a negative and significant effect on the level of the human development index in NTB. It is proven that the value of Fcount is greater than the value of Ftable (185.229 > 3,288) by using a significance limit of 0.05 (5%). Islam gives views on unemployment, including awareness of every Muslim, seeking opportunities, availability of public facilities, facilitating licensing, eradicating mafia, utilizing resources and establishing friendship. Likewise with poverty, Islam advises not to be lazy, not stingy, always give charity, infaq and zakat, be frugal.